Intralesional infiltration versus parenteral use of meglumine antimoniate for treatment of cutaneous leishmaniasis: A cost-effectiveness analysis. - Nayara C Brito; Tália S Machado de Assis; Ana Rabello; Gláucia Cota (Public Library of Science (PLoS), 2019)
Cutaneous leishmaniasis (LC) is a complex and variable disease in terms of epidemiology, aetiology, pathology and clinical characteristics. The mainstay of treatment is still pentavalent antimony (Sbv) compounds administered systemically, despite their recognized toxicity. The advantages of antimony intralesional (IL) infiltration are the use of lower doses of Sbv and, therefore, less toxic effects. The objective of this study was to estimate the cost-effectiveness ratio of intralesional meglumine antimoniate therapy (IL-MA) compared with endovenous meglumine antimoniate therapy (EV-MA) for the treatment of CL in the context of the Brazilian National Health System (SUS). An analytical decision model (decision tree) was developed using TreeAge Pro 2018 software. Data from the open-label, uncontrolled phase II clinical trial evaluating IL-MA were used as a reference for posology, efficacy, and adverse event rates (AE). The same premises for the intravenous approach (EV-MA) were extracted from systematic literature reviews. Macro and micro calculations of spending were included in the analysis. The IL-MA and EV-MA strategies had a total cost per patient cured of US$330.81 and US$494.16, respectively. The intralesional approach was dominant, meaning it was more economic and effective than was endovenous therapy. The incremental cost-effectiveness ratio showed that IL-MA could result in savings of US$864.37 for each additional patient cured, confirming that the IL-MA strategy is cost effective in the context of the Brazilian public health scenario.